Failure Mode and Effect Analysis and Analytic Hierarchical Process Applied for Reduction of Environmental Risk in Supplier Selection to Thermoplastic Industry - da Silva, Flavia Cristina; Shibao, Fabio Ytoshi; Librantz, Andre Felipe Henriques; Neto, Geraldo Cardoso de Oliveira; Nagaki, Lincoln (Journal of Environmental Accounting and Management, 2026)
Risk management has become a key issue for managing the green supply chain due to fact that the multi-risk and human judgment-based factors always involve subjectivity and ambiguity. Thus, Failure Mode Effects Analysis combined to Analytic Hierarchical Process was proposed for risk reduction in the selection process of suppliers of the green supply chain, providing flexibility and robustness in decision-making process. The tool was applied in the selection of flexographic solvent suppliers in an industry of the thermoplastic components segment and cold starting subsystems for the automotive industry, offering the opportunities for improvement in the monitoring supplier's performance.